Upaya Hukum untuk Mencegah Sengketa terhadap Debitur yang Mengalihkan Kredit Pemilikan Rumah Melalui Cessie - Nur`ainy Agmilya Sasmitha; Ahmad Heru Romadhon (Journal of Legal, Political, and Humanistic Inquiry, 2026)
The transfer of Home Ownership Credit (Kredit Pemilikan Rumah) through cessie constitutes a legally recognized mechanism for the assignment of receivables, yet it frequently generates legal disputes when debtor protection is inadequately ensured. This study examines legal efforts aimed at preventing disputes arising from the transfer of mortgage credit through cessie, with a particular focus on the position of debtors. Using a normative juridical approach, the research analyzes statutory regulations, legal doctrines, and relevant court decisions related to receivables transfer and security rights. The findings reveal that disputes commonly emerge due to insufficient notification to debtors, procedural deficiencies in the execution of cessie, and ambiguities concerning the continuity of mortgage guarantees. Preventive legal measures, including contractual clarity, compliance with statutory requirements, and strengthened institutional oversight, play a crucial role in reducing dispute potential. When preventive mechanisms fail, repressive legal remedies through litigation and alternative dispute resolution function as corrective instruments to restore legal balance. The study concludes that an integrated legal framework combining preventive and repressive measures is essential to ensure legal certainty and effective debtor protection in cessie-based mortgage transfers.